Non-Invasive Geophysical Investigation of Failure Along a Section of Ago-Iwoye Market Road, Ago-Iwoye, Southwestern Nigeria - MOSURO, Ganiyu Omotola; DADA, Oluwaseyi John; BAYEWU, Olateju Olatunji; OLORUNTOLA, Moroof Olasunbo; ODUGBESAN, Oluwadamilare Oluwatobiloba (GeoScience Engineering, 2023)
A detailed geophysical investigation was carried out to determine if the subsurface geology is responsible for the failures along this road section. This study aims to image and identify competent, moderately competent, and incompetent zones of the subsurface soil and thus to find out if geology is responsible for the failure along this section of the road. Electrical Resistivity Imaging (ERI) using the Wenner array 2D Imaging, and Vertical Electrical Sounding (VES) using the Schlumberger array were adopted for this survey. The geoelectric section from the VES revealed the presence of 3 lithological layers; topsoil, weathered layer (clay, sandy clay, clayey sand), and basement, which is also true for the electrical resistivity images revealed by the 2D electrical resistivity imaging. The results showed that the shallow subsurface beneath the road section is mostly underlain with clay that is geotechnically incompetent and not suitable for construction. The causes of road failure are believed to be the result of the incompetent clayey topsoil and the weathered layer seen in the profiles, which expand when absorbing water and shrink when drying, thus causing instability beneath the pavement due to the low shear strength and high compressibility, and also due to fractured basement rocks at shallow depths. Keywords: Basement; Clay; Resistivity; Road failure, Subsurface; Topsoil.